2006
DOI: 10.1111/j.1365-2524.2006.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Taking the call-bell home: a qualitative evaluation of Tele-HomeCare for children

Abstract: Tele-HomeCare (THC) delivers health care at home using telephone technologies. A THC service was developed as an adjunct to existing hospital and community care systems. It connected healthcare providers to children and families at home, during the initial transition from hospital to home, using video-conferencing phones and remote vital signs monitors. The goal was to support the transition from hospital to home, for children with subacute healthcare needs. This paper reports the qualitative evaluation of THC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…It also facilitates resolution of more minor problems which cause considerable parental anxiety, and when presented to the non-specialist in primary and secondary care settings, may result in hospital admission. There are several important advantages to keeping these vulnerable patients at home: avoiding exposure to infections in crowded waiting areas and hospital wards, and minimising family disruption, particularly, associated with hospitalising a child 21. Parents feel confident that their baby has been clinically assessed by a health professional familiar with the anatomy, physiology and ongoing health issues particular to their baby.…”
Section: Discussionmentioning
confidence: 99%
“…It also facilitates resolution of more minor problems which cause considerable parental anxiety, and when presented to the non-specialist in primary and secondary care settings, may result in hospital admission. There are several important advantages to keeping these vulnerable patients at home: avoiding exposure to infections in crowded waiting areas and hospital wards, and minimising family disruption, particularly, associated with hospitalising a child 21. Parents feel confident that their baby has been clinically assessed by a health professional familiar with the anatomy, physiology and ongoing health issues particular to their baby.…”
Section: Discussionmentioning
confidence: 99%
“…19 A study in children with subacute health-care needs showed that video played an important role during the early stages at home, enabling parents to become confident in caring for their child, and helping them to establish a strong rapport with the health-care providers. 20 Although videoconferencing can give the feeling of meeting the family, it cannot totally replace face-to-face visits. 21 It is important to bear in mind that if telemedicine was used as a replacement for standard care, instead of being used just as an adjunct, then the positive results might not be replicated.…”
Section: Discussionmentioning
confidence: 99%
“…The technology also provided family members from other states to see the baby, further connecting the family [26]. Home videoconferencing has also been shown to be successful in the postoperative management of children recently discharged with complex congenital heart disease [15, 27] as well as other complex diagnoses [15, 2830] with a high degree of parent satisfaction [31]. …”
Section: Discussionmentioning
confidence: 99%